Eksperimen Pembelajaran Matematika Pada Bangun Ruang Sisi Lengkung Dengan Menggunakan Pendekatan Realistic Mathematic Education Ditinjau Dari Motivasi Belajar Siswa Kelas IX SMP Negeri 1 Colomadu Tahun Ajaran 2015/2016 - Sudarman, Oki Hendra; , Drs. Sumardi,M.Si (2015)
The aim of research to understanding: (1) the difference of mathematics learning with Realistic Mathematics Education and Convensional based to mathematics achievement, (2) the difference of student's motivate to mathematics achievement, (3) the interaction between learning and student's motivate to mathematics achievement. The type of the research is experiment with quasi experimental design. The population of the research was all students of IX Grade of SMP Negeri 1 Colomadu of odd semester of academic year 2015/2016. The research sample consisted of two classes. The sampling technique use cluster random sampling. Methods of data collection use the test, questionnaires, and documentation. Data were analyzed use analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is a difference between the effect of Realistic Mathematics Education and Convensional based to mathematics achievement, with FA = 49,37 (2) there are differences in the effect of student's motivate for mathematics achievement, with FB = 12,41 (3) there is no interaction Realistic Mathematics Education and Convensional with student's motivate to mathematics achievement, with FAB = 0,61.